2000 IEEE International Reliability Physics Symposium Proceedings. 38th Annual (Cat. No.00CH37059)
DOI: 10.1109/relphy.2000.843884
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for voltage driven breakdown models in ultrathin gate oxides

Abstract: We have performed an experiment proving that the widely accepted E-field TDDB model is a physically incorrect description of breakdown in ultrathin gate oxides. Although interface traps are the dominant SILC mechanism below 5 V stress, breakdown remains limited by bulk trap generation and is voltage-driven. It has been recently proposed that the anode hole injection model is still operative at low voltages. Although we will show that holes do generate bulk traps and cause breakdown in ultrathin oxides, hole in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…Therefore, correlates with the electron energy not the oxide field. This was also demonstrated for conventional Fowler-Nordheim stress by varying the doping of the anode [34], [95]. The SHE experiments also showed that is inversely related to the current density [93], again showing that breakdown is dominated by the effect of the energetic electrons and not the field in the oxide.…”
Section: Physical Models For Defect Generationmentioning
confidence: 55%
See 2 more Smart Citations
“…Therefore, correlates with the electron energy not the oxide field. This was also demonstrated for conventional Fowler-Nordheim stress by varying the doping of the anode [34], [95]. The SHE experiments also showed that is inversely related to the current density [93], again showing that breakdown is dominated by the effect of the energetic electrons and not the field in the oxide.…”
Section: Physical Models For Defect Generationmentioning
confidence: 55%
“…A recent modification of the AHI model [68], [69] proposes that a weaker minority carrier ionization process [70] is responsible for hole injection and defect generation at low voltages. This mechanism will be operative for electron injection into a p-type material or hole inversion layer, and was observed for n-FETs with low gate doping when the n-poly gate inverted [34]. The modified model can successfully fit the measured slope of -versus-voltage at high fields [67], [69] but cannot account for the absolute magnitude of the defect generation rate.…”
Section: Physical Models For Defect Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the devices have the same threshold voltage, the effective stressing condition is the same for both groups of samples. Note that breakdown of thinner gate oxide occurs by bulk trap generation, not by interface trap generation, and is therefore driven by gate voltage [25]. With PCT Mo sputtering, the gate oxide integrity is significantly improved; indicating that low sputtering damage to gate dielectric is achieved.…”
Section: A Mo Sputter Depositionmentioning
confidence: 99%
“…Nonetheless it was refuted by several authors [27]- [30]. A major endorsement of the power law model, however, came from the experimental work performed by Nicollian et al [31]. The latter showed that the time to breakdown did not reduce after decreasing the doping in the poly silicon gate.…”
Section: Introductionmentioning
confidence: 99%